‘Double Bubble’ Technique for Successful Reattachment of Total Descemet Membrane Detachment after Deep Anterior Lamellar Keratoplasty - Titiyal, Jeewan S.; Kaur, Manpreet; Tinwala, Sana; Falera, Ruchita (Nepalese Journal of Ophthalmology, 2018)
Background: A double anterior chamber may be observed after deep anterior lamellar keratoplasty (DALK) and the management may be difficult especially in cases with a total descemet membrane detachment (DMD). Case Observations: We describe a novel “reverse double bubble” surgical technique for safe and effective reattachment of total DMD following DALK. Total DMD with air bubble in the interface was noted on the first postoperative day following DALK for healed keratitis. Intracameral air was injected via a 30-gauge needle inserted through a partial thickness MVR entry made at the posterior limbus, without disturbing the interface air-bubble. During this maneuver, the interface bubble did not change in size and moved towards the centre. The two distinct air bubbles, one in interface and other in anterior chamber indicated that air injection was in the anterior chamber, as per the reverse double bubble technique. The interface air bubble was removed by gently milking with an iris repositor towards the end of surgery. Thus, successful reattachment of DM was achieved despite difficult assessment of the plane of injection with the DM lying fl at on the surface of the iris. Conclusion: The reverse double bubble technique aids in the safe and successful reattachment of total DMD following intraocular surgeries.